Monitoring heart rate and body temperature using wireless technology (Zigbee) - Daud, H. (2014)
Wireless technology has increasingly emerged as one of the demanding technologies in healthcare industry. Monitoring patients' condition is a crucial task in any hospital to ensure patients are in good and stable condition. Wireless sensor network is the solution and has been widely introduced in measuring vital signs of patients such as temperature, heart rate, oxygen saturation, respiratory rate and others from remote location. Zigbee Network or accurately known as IEEE 802.15.4/Zigbee on the other hand is known to be a low power consumption device with good and stable data transmission range, higher network flexibility and large number of nodes. This work is discussing on integrating heart rate and temperature sensors to a wireless transceiver Zigbee (Xbee) module and is used to measure patients' conditions from remote location (nurse's station). Series of tests have been conducted using these devices to measure patients' heart rate and body temperature for different genders and age group at lying down position. This is to ensure that the devices developed are reliable, stable and producing the same results as conventional devices (thermometer and heart beat reader). Results obtained are very encouraging; the developed devices are producing stable readings and are capable of transmitting information at reasonable distance. Â© (2014) Trans Tech Publications, Switzerland.